Investigation of electromagnetic wave propagation characteristics across various frequencies in porous media of goaf. - Qingsong Zhang; Weikang Zhao; Hui Zhuo; Long Lin; Zuojian Li (PLoS ONE)
The reliable long-distance transmission of electromagnetic wave signals within goaf is fundamental for the implementation of wireless monitoring and early warning systems for goaf-related disasters. This paper establishes an experimental platform for electromagnetic wave signal transmission within goaf and develops a propagation model for electromagnetic waves in the porous media of goaf. The transmission characteristics of electromagnetic waves at various frequencies within the porous media environment of goaf are investigated through experimental and numerical simulation approaches. The results indicate that the received signal intensity of electromagnetic waves across different frequency bands diminishes with increasing propagation distance in the lossy environment of the goaf. Initially, the decay follows a logarithmic pattern, whereas, at later stages, the attenuation exhibits a gradual and smooth decrease. As the frequency increases, the initial attenuation amplitude of electromagnetic wave intensity rises; however, subsequent attenuation is largely unaffected by frequency, with the later attenuation rate being proportional to porosity. Electromagnetic waves at a frequency of 700 MHz exhibit a low attenuation coefficient under both experimental and simulated conditions, demonstrating superior stability and reliability. This frequency significantly enhances the overall performance of the communication system and is suitable for use as the operational frequency band in wireless sensor networks.